The Existence of Oil Palm Plantations and Challenges for the Riau Provincial Government - Geovani Meiwanda; Almasdi Syahza; Isnaniah Isnaniah (Ilomata International Journal of Social Science, 2022)
Palm oil is a commodity with considerable potential, in contributing to profits for Riau Province. Oil palm plantations that grow in Riau Province are owned by several companies and have grown into smallholder plantations. This means that the situation of Palm Oil Commodities in Riau Province is the primary supplier of economic value. On the other hand, Palm Oil Commodities that have grown for many years in Riau Province are in the Peatland area, which has a large potential for burning due to the character of land clearing which is mostly done by burning. This article is the result of research conducted simultaneously, by conducting qualitative research methods supported by primary and secondary data that strengthen the analysis. Riau without smog is difficult to escape, and it is always lucky if it enters the rainy season so that the disaster is not visible and the situation will be very different if it enters the long dry season. The existence of the environment is indeed difficult to go hand in hand with the existence of economic value generated from palm oil commodities.